Cefiderocol protects against cytokine- and endotoxin-induced disruption of vascular endothelial cell integrity in an in vitro experimental model - Hildebrand, Dagmar; Böhringer, Jana; Körner, Eva-Maria; Chiriac, Ute; Förmer, Sandra; Sähr, Aline; Hoppe-Tichy, Torsten; Heeg, Klaus; Nurjadi, Dennis (Antibiotics, 2022)
The severe course of bloodstream infections with Gram-negative bacilli can lead to organ dysfunctions and compromise the integrity of the vascular barrier, which are the hallmarks of sepsis. This study aimed to investigate the potential effect of cefiderocol on the barrier function of vascular endothelial cells (vECs) in an in vitro experimental set-up. Human umbilical vein cells (HUVECs), co-cultured with erythrocyte-depleted whole blood for up to 48 h, were activated with tumor necrosis factor-alpha (TNF-α) or lipopolysaccharide (LPS) to induce endothelial damage in the absence or presence of cefiderocol (concentrations of 10, 40 and 70 mg/L). The endothelial integrity was quantified using transendothelial electrical resistance (TEER) measurement, performed at 0, 3, 24 and 48 h after stimulation. Stimulation with TNF-α and LPS increased the endothelial permeability assessed by TEER at 24 and 48 h of co-culture. Furthermore, cefiderocol reduces interleukin-6 (IL-6), interleukin-1β (IL-1β) and TNF-α release in peripheral blood mononuclear cells (PBMCs) following LPS stimulation in a dose-dependent manner. Collectively, the data suggest that cefiderocol may have an influence on the cellular immune response and might support the maintenance of vEC integrity during inflammation associated with infection with Gram-negative bacteria, which warrants further investigations.